Lateral-Entry Pin Fixation in the Management of Supracondylar Fractures in Children - Skaggs, David L.; Cluck, Michael W.; Mostofi, Amir; Flynn, John M.; Kay, Robert M. (Journal of bone and joint surgery. American volume, 2004)
BackgroundThere has been controversy regarding the optimal pin configuration in the management of supracondylar humeral fractures in children. A crossed-pin configuration may be mechanically more stable than lateral pins in torsional loading, but it is associated with a risk of iatrogenic injury to the ulnar nerve. Previous clinical studies have suggested that lateral pins provide sufficient fixation of unstable supracondylar fractures. However, these studies were retrospective and subject to patient-selection bias.MethodsA displaced supracondylar humeral fracture was fixed with only lateral-entry pins in 124 consecutively managed children. Medical records and radiographs were reviewed to identify any complications, including loss of fracture reduction, iatrogenic ulnar nerve injury, infection, loss of motion of the elbow, and the need for additional surgery. In addition, eight displaced supracondylar humeral fractures that had been reduced and fixed with lateral pins at other institutions and had lost reduction were analyzed to determine the causes of the failures.ResultsSixty-nine children had a type-2 fracture, according to Wilkinsʼs modification of Gartlandʼs classification system; forty-three (62%) of those fractures were stabilized with two pins and twenty-six (38%), with three pins. Fifty-five children had a type-3 fracture; nineteen (35%) of those fractures were stabilized with two pins and thirty-six (65%), with three pins. A comparison of perioperative and final radiographs showed no loss of reduction of any fracture. There was also no clinically evident cubitus varus, hyperextension, or loss of motion. There were no iatrogenic nerve palsies, and no patient required additional surgery. One patient had a pin-track infection. Our analysis of the eight clinical and radiographic failures of lateral pin fixation that were not part of the consecutive series showed that the loss of fixation was due to fundamental technical errors.ConclusionsIn this large, consecutive series without selection bias, the use of lateral-entry pins alone was effective for even the most unstable supracondylar humeral fractures. There were no iatrogenic ulnar nerve injuries, and no reduction was lost. The important technical points for fixation with lateral-entry pins are (1) maximize separation of the pins at the fracture site, (2) engage the medial and lateral columns proximal to the fracture, (3) engage sufficient bone in both the proximal segment and the distal fragment, and (4) maintain a low threshold for use of a third lateralentry pin if there is concern about fracture stability or the location of the first two pins.Level of EvidenceTherapeutic study, Level IV (case series [no, or historical, control group]). See Instructions to Authors for a complete description of levels of evidence.